The impact of reflective practices on pre-service science teachers’ classroom teaching practices - Aygün Kılıç (Journal of Pedagogical Research, 2022)
This case study attempts to explore the impact of the reflective practices (reflection in, on, and for action) on pre-service science teachers’ (PSTs’) classroom teaching practices. To this end, ten PSTs majoring in Science Teacher Education Program participated in this study. In the study, the author designed a classroom teaching practice process based on reflective practices. This process was carried out during the teaching practicum course with the pre-service teachers participating in the research. At the beginning and end of the study, classroom observations, field notes, classroom observation instruments, teaching video records, and lesson plans were used as data collection tools in determining PSTs' classroom teaching practices. The qualitative and quantitative results of this study indicated that there was a significant change in favor of post-classroom practice results between PSTs' pre- and post-classroom teaching practices. Given these results, the classroom practice process based on the reflective practices carried out in the research plays an important role in the development of PSTs' classroom teaching practices.